La distribució de les vocals mitjanes tòniques en el català central - Mascaró, Joan (Caplletra. Revista Internacional de Filologia, 2008)
Mid vowels in stressed position are either closed ore open in Central Catalan, depending on a number of factors. In this paper we examine and discuss several of the proposals in the literature (general tendency towards lowering, influence of the immediate right consonantal context, lowering effect by the presence of a highfront vocoid in the following syllable(s), analogical effects stemming from the existence of phonologically similar elements in the lexicon, and metapaphonic effects caused by a following unstressed mid closed vowel. These independent factors cause a certain predominance of mid open vowels in cases of indeterminacy, but a general tendency toward open mid vowels based on a tendency to increase sonority is shown to be unjustified.